Calculated radiance errors induced by neglecting the polarization of the irradiation beam exposed to an atmosphere. (July 2020) - Wang, Cun-Hai
Highlights: Calculated radiance errors induced by neglecting the polarization of the incident irradiation reach up to 94.00%. Neglecting the linear polarized component induces much larger errors than neglecting the circularly polarized component of the incident beam. Diffuse reflection weakens the calculation errors for the boundary reflected radiance. Abstract: The radiance calculation via the solution of the scalar approximation form of the rigorous vector radiative transfer equation (VRTE) leads to non-negligible errors in atmospheric radiative transfer problems. In this work, for the first time, a quantitative investigation of the calculated radiance errors induced by neglecting the polarization of incident irradiation beams exposed to a plane-parallel atmosphere is presented. The discontinuous finite element method, which is highly accurate in the spatial and angular spaces, was employed to solve both the VRTE and its scalar approximation. The calculated values of the radiance obtained via the scalar model are compared with the exact solutions calculated via the vector model and their relative errors are analyzed. The results show that neglecting the linearly polarized component of the incident irradiation leads to relative errors up to 94.00%. These values are much larger than the errors induced by neglecting the circularly polarized component.